Chili Pepper as a Functional Food: Relevance to Lesotho - Sello, Mamakase; Lekatsa, Teboho (International Journal of Food Sciences, 2023)
Purpose: Although the use of chili peppers as functional foods in Lesotho is not well documented, their production and consumption have a rich historical background. Functional foods are those that serve as therapeutic agents in addition to nutrition. Previous research supports the many health benefits of consuming chili peppers, including their potential to mitigate the risk of cancer, cardiac arrhythmias, rheumatism, and chest colds. Nevertheless, these concepts have yet to translate into tangible alterations in policies and implementation strategies. Therefore, this review aims to identify potential topics for future research on Chili peppers, food, and therapeutic food product development; to improve the population's health and well-being Methodology: This paper presents a literature analysis of existing data on chili peppers as functional foods, specifically emphasizing their applicability to Lesotho, a developing country. Findings: Based on the analysis of the reviewed research, it can be inferred that those who regularly incorporate chili peppers into their diet exhibit a decreased risk of death from non-communicable diseases compared to those who do not. Unique Contribution to Theory, Practice and Policy: The data presented in this review supports the classification of chili pepper as a functional food while also emphasizing the importance of investigating the effectiveness, safety, quality, development, and possible hazards of chili peppers, particularly in developing nations like Lesotho. The present study has great potential to provide novel global perspectives on the associations between chili peppers, non-communicable diseases (NCDs), and mortality to guide future research. Hence, future research endeavors must thoroughly examine the distinct impacts of chili peppers through more clinical studies. Moreover, the present review and further research will contribute to revising Lesotho's dietary guidelines and advancing functional food products, such as herbal supplements derived from chili peppers.